Porcine reproductive and respiratory syndrome virus seroprevalence in Scottish finishing pigs between 2006 and 2018. (31st May 2021) - Correia‐Gomes, Carla; Duncan, Andrew; Ward, Allan; Pearce, Michael; Eppink, Lysan; Webster, Grace; McGowan, Andy; Thomson, Jill
Abstract: Background: Porcine reproductive and respiratory syndrome (PRRS) is a major endemic pig disease worldwide and is associated with considerable economic costs. Methods: In Scotland, three abattoir surveys were conducted in 2006 (158 farms), 2012‒2013 (94 farms) and 2017‒2018 (97 farms) to estimate seroprevalence to PRRS virus (PRRSV) in commercial finishing pigs. These surveys covered around 79%, 59% and 66% of the Quality Meat Scotland assured farms slaughtering pigs in Scotland in 2006, 2012–13 and, 2017–18 respectively. In the 2006 survey, six pigs per farm were sampled and tested using the CIVTEST SUIS PRRS E/S test. In the 2012‒2013 and 2017‒2018 surveys, 10 pigs per farm were sampled and tested using the IDEXX PRRS X3 Ab test. A farm was considered positive if it had one or more seropositive samples. Results: The prevalence of positive farms was 45.6% (95% CI: 38.0–53.4), 47.8% (95% CI: 38.1–57.9) and 45.4% (95% CI: 35.8–55.3) in the 2006, 2012‒2013 and 2017‒2018 surveys, respectively, and 70%–75.5% farms did not change their status between sampling periods. Conclusion: The prevalence of PRRSV exposure in Scottish pig herds was high and changed little from 2006 to 2018. These surveys have informed planning for a prospective PRRS control programme in Scotland.